García-Huidobro Joaquín, Una locura bastante razonable, Santiago de Chile, Editorial Andrés Bello, 2003, ISBN: 956-13-1830-X, 208 pp. - Crespo, Ricardo F. (2005)
Fil: Crespo, Ricardo F. Universidad Austral; Argentina